2011
DOI: 10.5194/acp-11-1961-2011
|View full text |Cite
|
Sign up to set email alerts
|

Forecasts and assimilation experiments of the Antarctic ozone hole 2008

Abstract: Abstract. The 2008 Antarctic ozone hole was one of the largest and most long-lived in recent years. Predictions of the ozone hole were made in near-real time (NRT) and hindcast mode with the Integrated Forecast System (IFS) of the European Centre for Medium-Range Weather Forecasts (ECMWF). The forecasts were carried out both with and without assimilation of satellite observations from multiple instruments to provide more realistic initial conditions. Three different chemistry schemes were applied for the descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 64 publications
2
36
0
Order By: Relevance
“…These results are similar to those found with IFS-MOZART by Flemming et al (2011). In the case of the BASCOE CTM, this is due to the absence of tropospheric processes and surface emissions, which prevents proper exchanges with the troposphere; and to the parameterisation of PSC surface area density, which lacks any memory of the coldness experienced by polar air masses.…”
Section: Bascoesupporting
confidence: 77%
See 2 more Smart Citations
“…These results are similar to those found with IFS-MOZART by Flemming et al (2011). In the case of the BASCOE CTM, this is due to the absence of tropospheric processes and surface emissions, which prevents proper exchanges with the troposphere; and to the parameterisation of PSC surface area density, which lacks any memory of the coldness experienced by polar air masses.…”
Section: Bascoesupporting
confidence: 77%
“…This indicates that IFS-MOZART has problems with a correct simulation of the ozone depletion. This is a known problem of the underlying MOZART CTM in the MACC configuration, which cannot be completely fixed by the data assimilation (Flemming et al, 2011;Inness et al, 2013), especially because the assimilated profile only gives information down to 68 hPa. MOZART performs better with WACCM meteorology (Kinnison et al, 2007), which indicates that the chemical parameterisations are sensitive to the meteorological fields that are used to drive transport in the models.…”
Section: Antarctic -Neumayermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, O 3 profile retrievals from MLS were assimilated together with O 3 total column retrievals from OMI, SBUV-2 and SCIAMACHY to exploit synergies of different instruments (Flemming et al, 2011). To reduce detrimental effects of inter-instrument biases, the variational bias correction scheme (Dee and Uppala, 2009) developed for the meteorological assimilation was adapted to correct multiple atmospheric composition retrievals.…”
Section: Case Study From Ecmwf: Macc Re-analysis Of Atmospheric Compomentioning
confidence: 99%
“…Advanced data assimilation allows the propagation of observational information in time and space and from a limited number of observed species to a wide range of chemical components and provides global fields that are physically and chemically consistent and in agreement with individual observations (Sandu and Chai, 2011;Bocquet et al, 2015). Various studies have demonstrated the capability of data assimilation techniques in the analysis of chemical species in the troposphere and stratosphere (e.g., Stajner and Wargan, 2004;Jackson, 2007;Parrington et al, 2009;Kiesewetter et al, 2010;Flemming et al, 2011;Coman et al, 2012;Inness et al, 2013;Emili et al, 2014;Miyazaki et al, 2012aMiyazaki et al, , b, 2014Miyazaki et al, , 2015Miyazaki et al, , 2017Miyazaki and Eskes, 2013;van der A et al, 2015;Gaubert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%